The Fluid Dynamic Basis for Actuator Disc and Rotor Theories Revised Second Edition - van Kuik, Gijs (TU Delft Open, 2022)
The first rotor performance predictions were published by Joukowsky exactly 100 years ago. Although a century of research has expanded the knowledge of rotor aerodynamics enormously, and modern computer power and measurement techniques now enable detailed analyses that were previously out of reach, the concepts proposed by Froude, Betz, Joukowsky and Glauert for modelling a rotor in performance calculations are still in use today, albeit with modifications and expansions. This book is the result of the author's curiosity as to whether a return to these models with a combination of mathematics, dedicated computations and wind tunnel experiments could yield more physical insight and answer some of the old questions still waiting to be resolved. Although most of the work included here has been published previously, the book connects the various topics, linking them in a coherent storyline. "The Fluid Dynamic Basis for Actuator Disc and Rotor Theories" was first published in 2018. This Revised Second Edition (2022) will be of interest to those working in all branches of rotor aerodynamics - wind turbines, propellers, ship screws and helicopter rotors. It has been written for proficient students and researchers, and reading it will demand a good knowledge of inviscid (fluid) mechanics.